Tensions, diplomatie et accommodations dans un espace partagé entre Saint-Pierre-et-Miquelon et Terre-Neuve, 1816-1842 - Landry, Nicolas (The Northern Mariner / Le marin du nord, 2017)
This article identifies the diplomatic parameters governing Anglo-French fishing activities in the shared coastal areas and fishing grounds near the archipelago of Saint-Pierre and Miquelon and the south-western coast of Newfoundland. The author first provides a background overview of the diplomatic negotiations on fishing rights between these two countries from 1778 onwards. He then examines the relations from 1816, looking at tensions as well as the accommodations aimed at maintaining calm in the fishing grounds.